2012
DOI: 10.1371/journal.pone.0042256
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Properties of Questionnaires Measuring Continuity of Care: A Systematic Review

Abstract: BackgroundContinuity of care is widely acknowledged as a core value in family medicine. In this systematic review, we aimed to identify the instruments measuring continuity of care and to assess the quality of their measurement properties.MethodsWe did a systematic review using the PubMed, Embase and PsycINFO databases, with an extensive search strategy including ‘continuity of care’, ‘coordination of care’, ‘integration of care’, ‘patient centered care’, ‘case management’ and its linguistic variations. We sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
98
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(105 citation statements)
references
References 40 publications
4
98
0
1
Order By: Relevance
“…Patient Reported Experience Measures proved to provide more information than patient satisfaction questionnaires by encouraging the users to describe their actual experience of the care received [11]. A review of the instruments measuring continuity of care showed that most available instruments on continuity of care from patients' perspective are designed to assess this construct in specific adult populations and settings, such as patients with diabetes, cancer, mental health problems, previously hospitalised patients, complex and chronic diseases, people being treated in primary care settings or patients in general regardless of morbidity or care setting [12]. To our knowledge, only one questionnaire has been developed to measure continuity of care in child population from the family's perspective, but it applies only to mental health care [13].…”
Section: Introductionmentioning
confidence: 99%
“…Patient Reported Experience Measures proved to provide more information than patient satisfaction questionnaires by encouraging the users to describe their actual experience of the care received [11]. A review of the instruments measuring continuity of care showed that most available instruments on continuity of care from patients' perspective are designed to assess this construct in specific adult populations and settings, such as patients with diabetes, cancer, mental health problems, previously hospitalised patients, complex and chronic diseases, people being treated in primary care settings or patients in general regardless of morbidity or care setting [12]. To our knowledge, only one questionnaire has been developed to measure continuity of care in child population from the family's perspective, but it applies only to mental health care [13].…”
Section: Introductionmentioning
confidence: 99%
“…This is a reliable and valid short questionnaire developed in Canada that Manitoba investigators modified for use at the time of discharge to pcp follow-up 43 . Delivering more highly evaluated scps should improve survivors' continuity of care [44][45][46] .…”
Section: Patient Continuity Of Care Questionnaire (Pccq)mentioning
confidence: 99%
“…Interestingly, engagement and retention in adult care correspond to 2 key challenges of transfer: ensuring continuity between pediatric and adult care, a type of "crossboundary continuity, " 42 and build a new patient-provider relationship (ie, initiate a new "relational continuity"). 43,44 Some authors have also considered informational continuity, corresponding to the availability of information about medical history to ensure appropriate care.…”
Section: Figurementioning
confidence: 99%
“…42 Their relevance to the transfer to adult care and their validity in youths with chronic diseases should be evaluated. Also, several authors suggested developing subjective measures of continuity.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation